PARTICIPATORY BUDGETING AS A TOOL FOR THE DEVELOPMENT OF LOCAL DEMOCRACY (ON THE EXAMPLE OF THE CITY OF KYIV) - Ruban , D. O (Theory and Practice of Public Administration, 2021)
The article investigates the origin of participatory budgeting in Brazil and the implementation of this mechanism in European countries and directly in the cities of Ukraine. Participatory budgeting is seen as one of the main tools for the development of local participatory democracy. The purpose, advantages and principles on which participatory budgeting is based are distinguished. The international experience in determining the main goal of participatory budgeting in communities has been analyzed. The indicators of efficiency which can be applied to an estimation of success of implementation in the city of Kiev of the public budget are proposed. Particular attention is paid to the implementation of the public budget in the city of Kyiv, the mistakes made at the stage of introduction of the institute of the public budget in the capital are analyzed. The process of functioning of the public budget in the city of Kyiv is also considered by systematizing information in the context of the main stages of implementation of the public budget initiative of the city of Kyiv (stages: submitting projects, conducting project evaluation, voting for projects) and identifying the main problematic issues that were formed during the entire period of implementation of the initiative in the capital. One of the most problematic and controversial issues has been investigated – the public availability of projects implemented within the framework of the public budget mechanism and the way to solve the problem has been proposed. Statistics and data of sociological researches have been collected and processed. That data demonstrate the dynamics of the development of the public budget in the city of Kyiv and show the attitude of Kyiv residents to this mechanism. Ways to solve certain problems on the basis of European and all-Ukrainian practice are also suggested.